2013
DOI: 10.1371/journal.pbio.1001648
|View full text |Cite
|
Sign up to set email alerts
|

A Meiosis-Specific Form of the APC/C Promotes the Oocyte-to-Embryo Transition by Decreasing Levels of the Polo Kinase Inhibitor Matrimony

Abstract: During the oocyte-to-embryo transition in Drosophila, degradation of the Polo kinase inhibitor, Matrimony, depends on Cortex, a meiosis-specific form of the Anaphase Promoting Complex/Cyclosome that is required for the oocyte's normal transition from meiosis to mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…Furthermore, we previously showed that at least one of its substrates, the Polo kinase inhibitor Matrimony, must be removed for proper embryogenesis (46). By defining the proteome of cortex mutant eggs, we identified proteins dependent on the CORT form of the APC for removal at egg activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we previously showed that at least one of its substrates, the Polo kinase inhibitor Matrimony, must be removed for proper embryogenesis (46). By defining the proteome of cortex mutant eggs, we identified proteins dependent on the CORT form of the APC for removal at egg activation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence conservation across lepidopterans and non-lepidopterans reveals a single binding site in cortex (Extended Data Fig. 9c) that probably binds the D box-like 18 degron LXEXXXN 19 . This degron binding capability is predicted for both of the full isoforms (1A (441 amino acids) and 1B (407 amino acids), although 1B apparently lacks the N-terminal C box that is usually required for APC/C binding) but not for the alternative isoforms (Extended Data Table 1).…”
Section: MMmentioning
confidence: 99%
“…The faithful segregation of genetic material into daughter cells during cell division is crucial for the production of healthy progeny (Jin et al, 2010;Whitfield et al, 2013;Teixeira et al, 2014). Chromosome segregation is regulated by several mechanisms, including cohesion degradation and SAC-dependent surveillance (Musacchio and Ciliberto, 2012).…”
Section: A Potential Role Of Cdc201 In Meiotic Chromosome Segregationmentioning
confidence: 99%